Exploring Factors Influencing Health Professionals’ Preparedness for Trauma Care in Accident and Emergency Departments in Selected Hospitals in Kakamega County, Kenya - Okwiri , Dinnah Akosa; Okoth, John Martin; Sum , Tecla Psusma (Medical Research and Its Applications Vol. 4, 2024)
Introduction: Trauma is a physical injury of sudden onset and severity to living tissue caused by an extrinsic agent and may result in wounds, broken bones, or internal organ damage. More than 9 people die every minute from trauma and 5.8 million people of all ages and economic groups die every year from accidental injuries. Trauma is a neglected disease of the modern world. Healthcare provider preparedness contributes to trauma patient survival. Purpose: The main objective of the study was to determine health professional factors influencing trauma care preparedness among health care providers working in the accident and emergency departments of the selected hospitals. Materials and Methods: This was a cross-sectional Analytic study. Census sampling was used to select General Practitioner hospitals. A systematic sampling technique was used to choose study participants from 11 selected hospitals. The study participants were 183 health professionals (Doctors, Clinical Officers and Nurses) working in the selected hospitals’ accident and emergency departments. Data was collected using structured questionnaires, and observation checklists. Data was analyzed using a statistical package for Social Science software version 22.0. Inferential statistics were used to test the strength of the association. Results: Health Professionals’ factors that influenced trauma care preparedness were; specific training on trauma care (p=0.002), attending Continuing Professional Development education (p=0.0008) and duration when last update was received (p= 0.04). Trauma care preparedness which was the study outcome was defined as a score of at least 50% on the four areas that were examined i.e. feeling on being prepared to attend to mass casualties, team performing a primary survey on trauma patients, having guidelines on the primary survey on trauma patients strongly agreeing that regular courses on trauma care are useful in preparation for trauma care with each having a score of 1 and overall expected score of 4.0. Conclusion: Trauma is influenced by trauma-related training, trauma-related continuing medical education, and the time since the last trauma update was received. Healthcare professionals who work in accident and emergency rooms must receive regular updates on trauma care as well as trauma-related training.